Preventing Chronic Obstructive Pulmonary Disease (COPD)The Role of Electric Smoking Alternatives: A Literature Review - Nurul Imam; Taufan Citra Darmawan; Khalifatus Zuhriyah Alfianti (Optimal Nursing Journal, 2025)
Introduction: The incidence rate of Chronic Obstructive Pulmonary Disease (COPD) remains high, especially in developing countries, with cigarette consumption being a major risk factor contributing to the prevalence of the disease. The purpose of this article review is to explain the role of e-cigarette alternatives in preventing COPD Method: A literature search was conducted in February 2025. The strategy used to search for articles is to use the PICOS framework. The article was identified with the keywords "(Chronic Obstructive Pulmonary Disease OR COPD) AND prevention AND (Electric Smoking Alternatives OR E-Cigarettes OR Vaping". with the 2019-2025 restrictions in English as well as full-text articles, so that relevant articles were obtained. Results: E-cigarettes (EC) and heated tobacco products (HTPs) offer significant reductions in exposure to toxic chemicals compared to conventional cigarettes, potentially reducing negative health impacts, including the risk of COPD exacerbations. Research shows that EC and HTP produce lower biological responses, such as inflammation and activation of stress markers in lung epithelial cells, which may reduce negative impacts on lung health.  Conclusion: E-cigarettes, show potential as a harm reduction strategy that can reduce exposure to harmful substances and help reduce cigarette consumption in COPD patients. Although EC has been shown to be effective in reducing cigarette consumption, its long-term effectiveness still needs more research, and there are concerns about the potential for smoking habit shifts in non-smokers.